2021
DOI: 10.3390/su13084148
|View full text |Cite
|
Sign up to set email alerts
|

Human Dimensions of Urban Blue and Green Infrastructure during a Pandemic. Case Study of Moscow (Russia) and Perth (Australia)

Abstract: Significant challenges of the COVID-19 pandemic highlighted that features of a modern, sustainable and resilient city should not only relate to fulfilling economic and social urban strategies, but also to functional urban design, in particular, related to urban blue and green infrastructure (BGI). Using results from a web-based questionnaire survey conducted May–July 2020 in Moscow (Russia) and Perth (Australia), this paper provides insights regarding citizens’ needs for and values of urban BGI as well as thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 45 publications
(89 reference statements)
3
51
0
Order By: Relevance
“…Given that a substantial proportion of our sample either had no access to traditional urban greenspaces such as parks (15%) during the first wave of the pandemic or rarely visited a formal greenspace (less than once a week−20%, never−17%; Table 1B), the role of open and informal spaces within residential neighbourhoods seems more relevant than ever before. Regional differences (economic regions and population density) in access to greenspaces as seen in our study (Figure 3), and parallel studies (e.g., Dushkova et al, 2021) further accentuate the need to consider alternatives. Planning for green-street elements could be beneficial for a multitude of outdoor activities at present, and in the long run.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Given that a substantial proportion of our sample either had no access to traditional urban greenspaces such as parks (15%) during the first wave of the pandemic or rarely visited a formal greenspace (less than once a week−20%, never−17%; Table 1B), the role of open and informal spaces within residential neighbourhoods seems more relevant than ever before. Regional differences (economic regions and population density) in access to greenspaces as seen in our study (Figure 3), and parallel studies (e.g., Dushkova et al, 2021) further accentuate the need to consider alternatives. Planning for green-street elements could be beneficial for a multitude of outdoor activities at present, and in the long run.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, to ensure social distancing, some cities decided to temporally or partially close urban parks, playgrounds and sports grounds for the public, leading to an increased pressure on other open spaces such as squares and streets. This situation highlighted the unequal distribution of and access to urban parks and gardens in cities during the pandemic (Shoari et al, 2020;Dushkova et al, 2021). Vice versa, home gardening showed an increase in its popularity, and both physical and mental health benefits are associated (Corley et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the potential benefits of parks are not realized equitably across all segments of society (Jennings et al, 2016). As research in countries such as Russia and Australia has shown (Dushkova et al, 2021), disparities in urban park use and access might be magnified in the era of COVID-19. Preexisting disparities, coupled with inequitable access to parks (a critical health promoting resource) during the pandemic, could exacerbate suffering and negative health outcomes in socially vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…During the lockdown, both the opportunity and capability of nature contact have been modified; however, the actual contact with nature may have been greatly influenced by personal motivations. The common positive, motivating factors for modified nature contact in terms of outdoor nature visits during lockdown included physically exercising, relaxing in nature, taking children outdoors, walking the dog, and meeting friends and family (Ugolini et al, 2020;Heo et al, 2021;Dushkova et al, 2021;Xie et al, 2020). In contrast, demotivating factors included over-crowding/distance concerns, lack of facilities (e.g., toilets in parks), not being able to meet with people outdoors, and difficulty accessing safe, publicly open green spaces in addition to the governmental rules to movement restrictions (O'Brien and Forster, 2021;Shoari et al, 2020).…”
Section: 4mentioning
confidence: 99%